Protestant missions in South America - Beach, Harlan Page (Young People's Missionary Movement of the United States and Canada, 1908)
Geographical and general by H.P. Beach -- British Guiana by F.P.L. Josa -- Dutch Guiana, or Surinam by J.T. Hamilton -- Brazil by H.C. Tucker --Republics of the Plata river by C.W. Drees -- Chile by I.H. La Fetra -- The land of the Incas by T.B. Wood -- Colombia by Mrs. T.S. Pond -- Venezuela by Mrs. T.S. Pond -- South America as a mission field by T.B. Wood.